PROFIL SIKAP ILMIAH SISWA SMP MUHAMMADIYAH 1 BERBAH PADA PEMBELAJARAN IPA - Buhera, Rusdiman (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aims to determine the scientific attitude level of students at SMP Muhammadiyah 1 Berbah. Using quantitative descriptive research methods, data was collected through scientific attitude questionnaires. The results showed that students' scientific attitude levels varied for each indicator, where curiosity obtained a score of 56 (medium level), critical thinking score 56 (medium level), respect for data/facts score 60 (medium level), open-mindedness score 58 (medium level), cooperation score 61 (medium level), and honesty achieved the highest score of 67 (high level). Overall, the average score of students' scientific attitudes was 59, at a medium level. Percentage analysis showed that no students were at low and very low levels (0%), the majority of students were at medium level with a percentage of 66% (128 students), followed by high level at 33% (64 students), and very high level at 0.5% (1 student).